Estimating the impact of child and early adolescent depression on subsequent educational attainment: secondary analysis of an existing data linkage. (25th November 2021) - Wickersham, A.; Ford, T.; Stewart, R.; Downs, J.
Abstract: Aims: Depression is thought to be associated with lower subsequent educational attainment during school. But, without longitudinal studies which take account of prior attainment and other potential confounders, estimates of the impact of clinically recognised depression in childhood and early adolescence are unknown. We investigated whether a clinical diagnosis of depression is associated with lower subsequent educational attainment, and whether the association is modified by gender, ethnicity and socioeconomic status. Methods: We conducted a secondary analysis of an existing administrative data linkage between national educational data and a large mental healthcare provider in London, UK (2007–2013). Depression diagnosis before age 15 (exposure) was measured from electronic health records, and subsequent educational attainment at age 15–16 (outcome) was measured from educational records. We fitted logistic regression models and adjusted for gender, ethnicity, socioeconomic status, relative age in school year, neurodevelopmental disorder diagnosis and prior attainment. We investigated effect modifiers using interaction terms. Results: In total, n = 63 623 were included in analysis, of whom n = 242 had record of a depression diagnosis before age 15. Depression was associated with lower odds of subsequently achieving expected attainment levels in national exams, after adjustment for all covariates (odds ratio = 0.60, 95% confidence interval = 0.43 to 0.84, p = 0.003). There was no evidence that gender, ethnicity or socioeconomic status modified this association. Conclusions: These findings support a relationship between depression and lower subsequent educational attainment. This highlights the need for tailored educational interventions to support children and adolescents with depression, particularly in the lead up to key educational milestones.